Dominique Darbois et la collection « Enfants du monde ». La photographie entre fiction et documentaire - Frédérique Lemarchant (Strenae)
Created in the 1950s by the publisher Nathan, the “Enfants du monde” collection introduced the photographic work of Dominique Darbois. Starting with the first published book in the collection, this article examines how the treatment of photography, the layout of the picture books, and the text/image relationship brought these documentary books closer to the fictional picture book. We will note in particular how the photographs of the main character encouraged an identification with the young reader, a determining mechanism in the reception of children's literature works.